Respostas

A melhor resposta!
2014-04-06T19:43:28-03:00
 x^{2} - 5x + 6 = 0
Δ = b² - 4 . 6
Δ = 25 - 24
Δ = 1

-b +-√Δ/2
5 +-1/2
x' = 3
x'' = 2

Belezinha?
2 5 2
2014-04-06T19:56:37-03:00
Alanabm , vc pode resolver de dois modos : por bháskara ou por soma e produto

Por bháskara :

Δ = 25 - 24
Δ = 1

x1 = 5 + 1 /2 
x1 = 3

x2 = 5 - 1 /2 
x2 = 2


Ou por soma e produto
 
S = -b /a = 5                  x1 = 2                  
P = c / a = 6                  x2 = 3

2 + 3 = 5            2.3 = 6
1 5 1